David Taylor, The Revised Statutes of the State of Wisconsin, as Altered and Amended by Subsequent Legislation, Together with the Unrepealed Statutes of a General Nature Passed from the Time of the Revision of 1858 to the Close of the Legislature of 1871, Arranged in the Same Manner as the Statutes of 1858, with References, Showing the Time of the Enactment of Each Section, and Also References to Judicial Decisions, in Relation to and Explanatory of the Statutes, at 1960–61, Of the Preservation of Fish and Game, § 37 (Vol 2, 1872) - (:unkn) unknown (General Publisher, 1871)
No person shall at any time or at any place within either of said counties, kill any wild duck, brant or wild goose, with or by means of the device, instrument or fire arm known as a punt or swivel gun, or with or by means of any gun or fire arm other than such guns or fire arms as are habitually raised at arm’s length and fired from the shoulder, or shall use any such device, instrument or gun other than such shoulder gun as aforesaid, with intent to kill any wild duck, brant or wild goose, under a penalty of fifty dollars for each and every offense.
--
Keywords: HUNTING REGULATION